Factor analysis to identify the dimension of Test of English Proficiency (TOEP) in the listening section - Retnawati, Heri; Munadi, Sudji; Al-Zuhdy, Yosa Abduh (REID (Research and Evaluation in Education), 2015)
This research is aimed at identifying the amount of the ability dimensions contained in the Test of English Proficiency (TOEP), particularly in the listening section. This study is an explorative descriptive quantitative research. The data of the study are the responses of the TOEP participants in the whole Indonesia in 2010, in some TOEP components. The participants are grade IX students of senior high schools. The collected data were gained from the data documentation of the Diretorate of Senior High Schools Founding of the National Education Ministry, Jakarta. The data analysis for identifying the dimension was done by implementing exploratory and confirmatory factor analysis. The exploratory factor analysis was done by using SPSS computer program. The result of the research shows that of the seven sets of listening which were analyzed, all of them contain listening dominant dimension if they are analyzed using graphics method, explainable variance, and Eigen value ratio.